Physico-Chemical Attributes of Soursop Fruits during Storage under Treatment of 1-Methylcyclopropene (1-MCP) - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2020)
Owing to high moisture content, soursop (Annona muricata) fruit has a short shelf-life by turning soft and bruised easily after harvesting. It quickly becomes unacceptable for fresh consumption. This valuable fruit should be preserved for a long shelf life. However, the lack of improved postharvest technology limits it on domestic and foreign markets. This research evaluated the effectiveness of 1-methylcyclopropene in different concentration (0, 50, 100, 150, 200 ppm) to shelf-life of soursop fruits during 12 days at ambient temperature storage. The use of this ethylene inhibitor at 150 ppm improved the shelf-life and quality of soursop fruit, including lower weight loss, maintain firmness, retent ascorbic acid and soluble solid during preservation Keywords: Soursop, 1-methylcyclopropene, Preservation, Firmness, Weight loss, Soluble solid, Ascorbic acid, Post-harvest.